MENINGKATKAN PEMAHAMAN KONSEP PADA MATERI STATISTIKA DENGAN MEDIA PEMBELAJARAN VIDEO INTERAKTIF PADA SISWA KELAS VIII SMP NEGERI 4 LIMBOTO - Abdulah, Siska; Hulukati, Evi; Nurwan, Nurwan; Ismail, Yamin; Zakiyah, Siti (Department of Mathematics Education, Universitas Kuningan, 2023)
This study aims to increase students' understanding of concepts using interactive video learning media on statistical material. The type of research used is classroom action and is carried out at SMP Negeri 4 Limboto in the even semester of the 2021-2022 academic year. The subjects of this study were 28. The assessments used in the study were teacher and student observation sheets and concept understanding tests. This research was conducted in 2 cycles. The average percentage of teacher observations from cycles I and II reached 70.8% and 80.8%, resulting in an increase of 10%. Furthermore, the average percentage of student observations reached 67.5% and 81.25% so that there was an increase of 13.75%. The results of the student's concept understanding test also increased from 64.29% to 82.14%. In cycle II, all aspects assessed have reached the indicators of learning success by using interactive video learning media